2016
DOI: 10.1080/08941939.2016.1240271
|View full text |Cite
|
Sign up to set email alerts
|

Which Suture Material is Optimal for Pancreaticojejunostomy Anastomosis? An In Vitro Study

Abstract: None of the suture materials was disintegrated on exposure to pancreatic juice, bile, and their mixture. Polyglactin 910 has the highest breaking strength and significantly loses its strength throughout the experiment but still remains higher than other suture materials. Polypropylene, polydioxanone, and silk showed less variation across the incubation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…In our work, all tests were performed with a single-axial electromagnetic Ultimate Tensile Machine (UTM)—Synergie 200H (MTS System Corporation, Eden Prairie, MN, USA) equipped with a load cell of 100N. The groups of Naleway et al, Karaman et al, and Gierek et al used similar machines and paid attention to settle the suture threads in order to let it break in the middle rather than next to the anchorage knot [ 31 , 35 , 45 ]. However, their system does not have a grip mechanism able to self-align the suture threads during the test, avoiding any misalignments and consequently errors during the acquisition of the stress–deformation curves used to evaluate the UTS and Young’s modulus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our work, all tests were performed with a single-axial electromagnetic Ultimate Tensile Machine (UTM)—Synergie 200H (MTS System Corporation, Eden Prairie, MN, USA) equipped with a load cell of 100N. The groups of Naleway et al, Karaman et al, and Gierek et al used similar machines and paid attention to settle the suture threads in order to let it break in the middle rather than next to the anchorage knot [ 31 , 35 , 45 ]. However, their system does not have a grip mechanism able to self-align the suture threads during the test, avoiding any misalignments and consequently errors during the acquisition of the stress–deformation curves used to evaluate the UTS and Young’s modulus.…”
Section: Discussionmentioning
confidence: 99%
“…Tensile tests were carried out through an Ultimate Tensile Machine (UTM) Materials Testing Systems—Synergie 200H (MTS System Corporation, Eden Prairie, MN, USA), which is a single-axial electromagnetic actuation machine equipped with a load cell of 100 N. To avoid misalignment of the suture threads during the test, two test grips were specifically designed. Standard test methods to characterize the properties of suture threads subjected to traction (ASTM D3822/D3822M-14 and ASTM D2256/D2256M-21) [ 40 , 41 ] were followed and integrated with the experiments presented in the literature [ 31 , 33 , 35 , 36 ] in order to create the test-specific protocol for this project.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for the choice of a specific suture material should be based on the effects of pancreatic juice and bile on the suture's mechanical features. Two studies 22,28 have explored the effect of both pancreatic juice and bile on the mechanical properties of different suture materials. These studies reported different results, although PDO appears to be the most resistant suture material.…”
Section: Discussionmentioning
confidence: 99%
“…Also, because of their structure, polyglycolic sutures were digested by nonactivated pancreatic juice faster than by activated pancreatic juice [9]. Furthermore, in numerous studies it was concluded that synthetic suture materials were better for use in pancreas surgery [15,16].…”
Section: Effect Of Pancreatic Juice and Bile On The Tensile Strength mentioning
confidence: 99%